THE USE OF TADALAFILIN PATIENTS WITH CHRONIC PROSTATITIS/CHRONIC PELVIC PAIN SYNDROME (Iraqi Journal of Medical Sciences, 2016)
Background:The treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) can be a frustrating challenge to physicians and many drugs had been used with variable results.Objective:To evaluate the safety and the efficacy of adding 5 mg tadalafil for patients with CP/CPPS with the conventional treatment.Methods:Thirty five patients received tamsulosin 0.4 mg capsule once daily, levofloxacin 500mg tablet once daily and indomethacin rectal suppository 100 mg once daily served as control group. Another 35 patients received the alpha blocker, levofloxacin and NSAID as above with tadalafil 5 mg once daily for 1 month period comprised tadalafil group. The NIH Chronic Prostatitis Symptom Index (NIH-CPSI) assessment was completed by each patient at baseline and 4 weeks after the drug therapy to assess the response to treatment. We consider in our study the chronic prostatitis/CPPS or category IIIa or b according to NIH classification system.Results:No significant difference in mean age and baseline score in between groups was found. After one month of starting treatment, it had been found that NIH-CPSI/pain, urinary and quality of life domains were significantly changed from (12.8±1.44, 5.9±1.77 and 8.8±1.82) at baseline to (9.6±1.04, 3.55±0.99 and 3.88±1.31) respectively in group A. In group B also there was a significant reduction in the NIH-CPSI among patients in this group; the baseline NIH-CPSI/pain, urinary and quality of life domains were (13.4±1.66, 5.8±1.85 and 9.3±1.92) and changed to (6.28±0.90, 2.65±0.86 and 2.69±1.43) respectively after treatment. The total NIH-CPSI was 27.5±4.78 and changed to 17.03±3.91 after treatmentin group A and 28.5±4.49 changed to11.62±3.59 in group B. Conclusion:The use of tadalafil in patients of CP/CPPS with conventional treatment for 1 month was safe and has high efficacy in reducing the symptoms for the patients and improving the quality of life.Keywords: Tadalafil, chronic prostatitis, chronic pelvic pain syndrome
Keywords: Tadalafil; chronic prostatitis; chronic pelvic pain syndrome